Does Entrepreneurship Education in Family Business Affect Entrepreneurial Attitudes and Motivation? - Muhammad Hasan; Thamrin Tahir; Nurdiana Nurdiana; Karuniana Dianta Arfiando Sebayang; Nur Fatwa (Faculty of Economics, State University of Jakarta., 2021)
The ability to survive a family business during the COVID-19 pandemic is a very interesting concept to study, because almost every family business has difficulty maintaining its business in the midst of the COVID-19 pandemic, so based on this, this study aims to analyze and reveal the influence of entrepreneurship education in family towards entrepreneurial motivation, either directly, or through mediating the entrepreneurial attitude of family business entrepreneurs in the culinary sector during the COVID-19 pandemic. This study is a non-experimental explanatory study on the culinary sector family business in Makassar City, South Sulawesi. The population in this study is 1,267 family businesses in the culinary sector, with a sample of 133 family businesses in the culinary sector. The findings of this study have succeeded in revealing and exploring that entrepreneurship education in the family has contributed to the formation of entrepreneurial motivation both directly and indirectly through mediating the entrepreneurial attitude of family business entrepreneurs in the culinary sector during the COVID-19 pandemic.